Endoscopic approach to hyperplastic laryngeal lesions: a literature review and personal experience - Petru Gurău (The Egyptian Journal of Otolaryngology, 2023)
Abstract Background Presently, there is a lot of confusion in the identification and classification and no consensus regarding the management of hyperplastic laryngeal lesions (HLL). Conventional transoral microsurgery has some drawbacks and is not always possible. The purpose of the study was to identify criteria for preoperative detection of HLL with high malignant potential and to assess the effectiveness of flexible endoscopic surgery (FES) in the management of HLL. Methods A review of relevant English literature and a retrospective review of medical records of 37 patients with HLL, treated by FES, was performed. Results Endoscopic and histologic features of HLL are discussed. An endoscopic classification of HLL is proposed: chronic hyperplastic laryngitis (CHL), chronic hyperplastic laryngitis with keratosis (CHLK), leukoplakia, pachydermia, and verrucous neoplasia. The role of FES using different tools in the diagnosis and management of HLL is presented. We applied flexible endoscopic laryngeal surgery (FELS) for 37 patients (ages, from 20 to 77 years, men 34, women 3) with the following types of HLL: CHLK 5, leukoplakia 18, pachydermia 12, verrucous neoplasia 2. Tracheostomy was offered in 1 case of obstructive verrucous neoplasia with subsequent decanulation after successful endoscopic management. According to the data from the literature and our own observations, the following criteria seem to point to a HLL with high malignant potential: verrucous neoplasia, pachydermia, a lesion affecting more than a half of the vocal fold, mucosal hyperemia, high-grade dysplasia in biopsy samples. The expected result (total eradication of the visible lesion) was obtained in all of our cases (mean follow-up period 76 months). Invasive carcinoma developed subsequently in 2 patients that continued to smoke after surgery. All the patients that could be followed-up stated an improvement of their voice after surgery. Conclusion The following criteria can be used for preoperative detection of HLL with high malignant potential: verrucous neoplasia, pachydermia, a lesion affecting more than a half of the vocal fold, mucosal hyperemia, high-grade dysplasia in biopsy samples. Flexible endoscopic surgery, preceded by large flexible forceps biopsy, is a good alternative for HLL management. Diathermy snare is a useful tool for the diagnosis and first-line treatment in selected patients.